Pengaduan oleh Korban Tindak Pidana Perzinaan: Studi Perbandingan Hukum Pidana dan Hukum Islam - Nasution, Ahmad Adanan; Harahap, Mar’ie Mahfudz (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
This study aims to comprehensively analyze the differences between the complaint system for victims of adultery in the new Penal Code and Islamic Criminal Jurisprudence. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The findings reveal fundamental differences between the two legal systems, despite a convergence in the expanded definition of adultery. The new Penal Code retains adultery as a complaint offense, allowing for the withdrawal of complaints before the trial examination begins. Conversely, Islamic Criminal Jurisprudence categorizes adultery as an ordinary offense, with complaints treated as da’wa (lawsuits) that, once proven, cannot be withdrawn due to their violation of Allah’s law. This distinction reflects a fundamental philosophical divergence between the two legal systems. The new Penal Code prioritizes protecting individual interests and providing room for reconciliation, while Islamic Criminal Jurisprudence emphasizes upholding moral values and divine justice. Therefore, it is recommended that law enforcement officers understand the philosophical differences and practical implications between the new Penal Code and Islamic Criminal Jurisprudence when handling adultery cases. Victims should understand their rights and the consequences of any legal action, including the possibility of reconciliation within the new Penal Code’s framework. Furthermore, society should enhance its understanding of both legal systems to actively participate in preventing and addressing adultery cases wisely and based on noble moral values, fostering a social environment conducive to peaceful and dignified conflict resolution.